2023
DOI: 10.3354/meps14230
|View full text |Cite
|
Sign up to set email alerts
|

Biological interactions potentially alter the large-scale distribution pattern of the small pelagic fish, Pacific saury Cololabis saira

Abstract: We aimed to understand the effect of biological interactions on the distribution of small pelagic fishes. Surveys were conducted during 2003-2019 using sea surface trawl nets in the western and central North Pacific Ocean, covering an area between 143° E and 165° W, to estimate the distributions of 4 small pelagic fishes: Pacific saury Cololabis saira, Japanese sardine Sardinops melanostictus, chub mackerel Scomber japonicus, and Japanese anchovy Engraulis japonicus. These species are potential competitors, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…Apart from the direct competition for food, Fuji et al. (2023) suggested that the dominant species would competitively exclude other species, forcing them to shift distribution, possibly leading to an increase in energy loss because of longer migration routes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Apart from the direct competition for food, Fuji et al. (2023) suggested that the dominant species would competitively exclude other species, forcing them to shift distribution, possibly leading to an increase in energy loss because of longer migration routes.…”
Section: Discussionmentioning
confidence: 99%
“…The common trends derived from the ‘medium‐term period’, which included more species and excluded the influence of abundant Japanese sardine populations in the 1980s, were negatively correlated with the summed biomass dominated by chub mackerel and Japanese sardine. Since 2013, the Japanese sardine and chub mackerel have been increasing in both the Pacific (Fuji et al., 2023) and the Sea of Japan (Kuroda et al., 2021a; Muko et al., 2021) and have dominated other species in biomass. This observation indicates that high stock levels of Japanese sardine and chub mackerel might trigger intra‐ and interspecies competition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations